PENERAPAN MODEL PEMBELAJARAN BLENDED LEARNING UNTUK MENINGKATKAN HASIL BELAJAR PADA MATA KULIAH FISIKA TERAPAN PPROGRAM STUDI D-3 TEKNIK MESIN UNIVERSITAS NEGERI JAKARTA - Dewi Nur Utami; Priyanto, Sugeng; Syaripuddin (LPPM, Universitas Negeri Jakarta, 2021)
This research aims to determine whether by applying Blended Learning learning models using Moodle applications can improve student learning outcomes of D-3 Mechanical Engineering in Applied Physics courses at Jakarta State University.The method used in this study is Classroom Action Research (CAR) which is a form of investigation conducted by participants involved in the situation under study. The action is followed by observation and reflection. If needed at a later stage, a followup plan is prepared. The effort was carried out in cycles to form one cycle. The place of research was conducted at Jakarta State University, and the research subjects were 29 Mechanical Engineering D3 students. The study was conducted on November 7, 2019 until December 26, 2019. Learning outcomes were obtained through written tests and then analyzed to compare exam results in each cycle.The results of this study indicate that an increase in student learning outcomes in Applied Physics courses by applying Blended Learning learning models using the Moodle application. Improved learning outcomes can be seen in Cycle I the average value of all students is 52.84 and only 51.72% or 15 students out of a total of 29 students who scored ≥60. In Cycle II the mean value of all students was 74.05 and 86.21% or 25 students out of a total of 29 students who scored ≥60. Researchers can conclude student learning outcomes have increased with the application of Blended Learning learning models using the Moodle application. Keywords: applied physics, blended learning, classroom action, learning outcomes, moodle